Model and Strategies for Curriculum Development in the Context of Arabic Language Learning (Arabic and English Education Journal, 2025)
The development of the Arabic language curriculum is an important matter that requires clarity to enhance educators' skills in delivering material presented in the classroom. Many incidents indicate that some educators are not understand and uninterested in the curriculum. This situation has a significant impact on the learning process; educators who are not familiar with the curriculum cannot guide students on learning, and the students will not be focused on learning. This research also aims to understand curriculum development, with a focus on curriculum development models and strategies, particularly in Arabic language teaching. The object of this research is the Arabic language curriculum. This study employs library research as a method and using a qualitative research approach. Curriculum development helps in designing a learning curriculum that can be tailored to the student,s need, adapted to the times, making learning more engaging, and preparing education so that students can face the workforce. This curriculum development requires models and strategies as guidelines to achieve specific goals. For example, competency-based curriculum development models and strategies aim to enable students to achieve specific competencies, such as reading classical and modern Arabic texts, or speaking Arabic in daily life or in an international context. However, this research does not further investigate the correlation between curriculum development models and their development strategies